The genus Doryctes Haliday, 1836 (Hymenoptera: Braconidae, Doryctinae) in China - Belokobylskij, Sergey A.; Tang, Pu; He, Jun-Hua; Chen, Xue-Xin (Zootaxa, 2012)
Thirteen Chinese species of Doryctes Haliday, 1836 are recognized. Four new species, D. flavistigma sp. nov., D. hain-anensis sp. nov., D. mayunae sp. nov., and D. yunnanicus sp. nov., are described and illustrated. Five species, i.e., D. ma-layensis (Fullaway, 1919), D. petiolatus Shestakov, 1940, D. striatellus (Nees, 1834), D. undulatus (Ratzeburg, 1852), andD. yogoi Watanabe, 1954, are recorded from China for the first time. A key to Chinese species of the genus Doryctes is provided.